Effects Effects of Breathing Exercises on Lung Volumes and Capacities Among Smokers - Zahra, Iman; Liaqat, Maria; Qadeer, Ummara (Jurnal Medis Islam Internasional, 2020)
Objective: To determine the effect of deep breathing exercises on lung volumes and capacities among smokers. Methodology: The participants were divided into a control group and an experimental group. The control group was not given any treatment, while the experimental group performed deep breathing exercise techniques. The experimental group performed exercises for six weeks. After six weeks lung function tests were performed to evaluate the effects. Data were compared at baseline and after the intervention. To check within the group's changes paired sample t-test was used. To check between groups changes independent sample t-test was used for normally distributed data. Results: In the experimental group, significant changes (p ≤ 0.05) were observed after the intervention. While comparing groups, significant differences (p ≤ 0.05) were observed in some variables between experimental and control groups.Conclusion: It was concluded that deep breathing exercises are useful among smokers. As deep breathing helps in improving lung volumes and capacities.